Island of Lost Souls Based on a Novel by H.G. Wells - Kenton, Erle C.; Struss, Karl; Laughton, Charles; Lugosi, Bela; Arlen, Richard (Eureka Video, 2012)
Regarded as the best screen adptation of H.G. Wells' classic novel "The Island of Dr Moreau" and banned in Britain for many years, "Island of Lost Souls" is a true classic of horror cinema from the early 1930s. Originally rejected by the BBFC on its original release for being 'against nature', "Island of Lost Souls" is one of Hollywood's wildest, most notorious, pre-Code pictures. A taboo-flaunting, blood-curdling spectacular, it is the first and best screen adaptation of H.G. Wells' "The Island of Dr. Moreau" ... Featuring a peerlessly sinister performance by Charles Laughton as the diabolical doctor, a sterling appearance by Bela Lugosi as the half-beast-half-man 'Sayer of the Law', and sensationally atmospheric cinematography by the great Karl Struss, "Island of Lost Souls" now returns to claim a central position among the most imaginative and nightmarish fantasies from Hollywood's golden age of horror. [www.moviemail.com]
Keywords: Blu-Ray-Disc